Climber Species Composition and Distribution Pattern along the Elevation Gradient of Courtallam Hills, Southern Western Ghats of India - Pandian, Elumalai; Ravichandran, Perumal (Indian Forester, 2024)
The pattern of climber species diversity, richness, structural characteristics and above-ground biomass (AGB) assessed along an elevation gradient from 200 to 1000 m in Courtallam hills, Southern Western Ghats of India. Five 1-ha plots (100x100 m) were inventoried in different elevations of the tropical montane forest: Old Courtallam (OC), Courtallam beat (CB), Pooncholai (PC), Therkumalai estate (TE), and Maillodai estate (ME), with elevational ranges are 200, 400, 600, 800 and 1000 m respectively. All climber species with â‰¥1 cm dbh (diameter at breast height) were measured at 130cm from ground level. A total of 3059 climber individuals (ranging from 412-828 individuals ha-1 in OC and ME respectively) representing 83 species and 63 genera under 31 families were enumerated in studied plots. The total basal area of climbers in these study sites was 4.6 m2 (ranging from 0.76 to 1.1m2 ha-1). The climber species viz. Pyrenacantha volubilis, Ziziphus oenoplia, Salacia oblonga, Piper argyrophyllum and Ancistrocladus heyneanus were dominant in plots OC, CB, PC, TE and ME respectively. The AGB showed 31.835 Mg/ha-1 in plot OC, 27.461 Mg/ha-1 in plot CB, 28.241 Mg/ha-1 in plot PC, 17.578 Mg/ha-1 in plot TE and 26.604 Mg/ha-1 in plot ME. This study, suggests that forest management and forest protection are vital for the in-situ conservation of climber diversity with the contribution of the local people.